Alkaline Phosphatase and Parathyroid Hormone Levels: International Variation and Associations With Clinical Outcomes in the DOPPS - Suguru Yamamoto; Hanne Skou Jørgensen; Junhui Zhao; Angelo Karaboyas; Hirotaka Komaba; Marc Vervloet; Sandro Mazzaferro; Etienne Cavalier; Brian Bieber; Bruce Robinson; Pieter Evenepoel; Masafumi Fukagawa (Kidney International Reports)
Introduction: Secondary hyperparathyroidism (SHPT) increases the risk of fractures and cardiovascular (CV) disease in patients on hemodialysis (HD). The relationship between parathyroid hormone (PTH) and outcomes has been inconsistent, possibly due to variable bone responsiveness to PTH. The KDIGO guideline suggests monitoring total alkaline phosphatase (ALP), but the role of ALP versus PTH in the management of mineral and bone disorder (MBD) is not clear. Methods: The analysis included 28,888 patients on HD in 9 countries in Dialysis Outcomes and Practice Patterns Study (DOPPS) phase 3 to 7 (2005–2021). The primary exposures of interest were normalized ALP and PTH, which are raw values divided by facility upper normal limit, measured at study enrollment. Cox models were used to estimate hazard ratios of all-cause or CV mortality and any or hip fracture adjusted for potential confounders. Linear mixed models, adjusted for potential confounders, were employed to investigate the relationship between normalized ALP levels and patient characteristics. Results: Normalized PTH showed a J-shaped association with all-cause or CV mortality, and a weak linear association with fracture. In contrast, normalized ALP showed a strong association with all outcomes. Factors associated with higher ALP levels after controlling for PTH included Black race, longer dialysis vintage, diabetes mellitus, hypocalcemia, hypophosphatemia, elevated C-reactive protein (CRP), and the use of cinacalcet. Conclusion: Total ALP is a more robust exposure of adverse outcomes than PTH in patients on HD. PTH responsiveness is affected by race, primary renal disease, comorbidities, and mineral metabolism and therapy. Our results indicate that it may be useful to evaluate target organ response, rather than PTH alone when considering the consequences of (SHPT).